2007
DOI: 10.1210/en.2006-1157
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Type 1-Mediated Vascular Oxidative Stress and Proinflammatory Gene Expression in Aldosterone-Induced Hypertension: The Possible Role of Local Renin-Angiotensin System

Abstract: Recently, aldosterone has been shown to activate local renin-angiotensin system in vitro. To elucidate the potential role of local renin-angiotensin system in aldosterone-induced cardiovascular injury, we investigated the effects of selective mineralocorticoid receptor (MR) antagonist eplerenone (EPL), angiotensin (Ang) II type 1 receptor antagonist candesartan (ARB), and superoxide dismutase mimetic tempol (TEM) on the development of hypertension, vascular injury, oxidative stress, and inflammatory-related ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 29 publications
5
101
1
2
Order By: Relevance
“…In addition, aldosterone itself has certain actions that are independent of Ang II stimulation. For example, aldosterone acts through AT 1 R to mediate vascular oxidative stress by increasing mRNA levels of reduced nicotinamide adenine dinucleotide phosphate oxidase components; this effect was abolished by selective MR antagonism, whereas AT 1 R blockade and tempol decreased only the p47 phox mRNA level but not that of p22 phox or gp91 phox (122). In the same study, MR antagonism uniformly abrogated aldosterone-mediated stimulation of proinflammatory genes, whereas AT 1 R blockade and tempol had gene-specific effects.…”
Section: B Role Of the Raas In Oxidative Stress And Hypertensionmentioning
confidence: 99%
“…In addition, aldosterone itself has certain actions that are independent of Ang II stimulation. For example, aldosterone acts through AT 1 R to mediate vascular oxidative stress by increasing mRNA levels of reduced nicotinamide adenine dinucleotide phosphate oxidase components; this effect was abolished by selective MR antagonism, whereas AT 1 R blockade and tempol decreased only the p47 phox mRNA level but not that of p22 phox or gp91 phox (122). In the same study, MR antagonism uniformly abrogated aldosterone-mediated stimulation of proinflammatory genes, whereas AT 1 R blockade and tempol had gene-specific effects.…”
Section: B Role Of the Raas In Oxidative Stress And Hypertensionmentioning
confidence: 99%
“…Furthermore, aldosterone increases oxidant stress, which in turn promotes vascular inflammation. In particular, aldosterone increases expression of the NADPH oxidase subunits p22phox and gp91phox in the aorta, leading to an increase in reactive oxygen species (28,29). Aldosterone also decreases endothelial expression of glucose-6-phosphate dehydrogenase (G6PD), leading to increased oxidant stress and decreased nitric oxide (NO) levels (30).…”
mentioning
confidence: 99%
“…This postulated mechanism could well explain our study results, with high-sodium intake potentially aggravating myocardial injuries induced by aldosterone through up-regulated oxidative stress. The hypothesis has been supported by previous studies, which showed that the development of hypertension and the regression of cardiovascular remodeling were attenuated in mineralocorticoid treated animals after the treatment of antioxidant drugs, such as the superoxide dismutase mimetic Tempol [21,22] , the NADPH oxidase inhibitor apocynin [23,24] or N-acetylcysteine [5] . Increased oxidative stress might also trigger and deteriorate inflammation.…”
Section: Discussionmentioning
confidence: 59%